Orel rozsápe orla Emil Filla, čínské umění a totalitní přízraky = Eagle rips eagle : Emil Filla, Chinese art and totalitarism phantoms - Pejčochová, Michaela 1977-; Winter, Tomáš 1974- (Ústav dějin uměni, Akademi věd České republiky, 2024)
The book is devoted to the post-war art of the Czech painter, sculptor and theoretician Emil Filla (1882-1953) and his relationship to Chinese art and the Communist ideology. It describes Filla’s unique collection of Chinese art and discusses its creation. It explores Filla’s understanding of Far Eastern painting that was reflected in his essays on Chinese landscape painting and his late-career paintings. These pictures in particular are given greater attention, notably with regard to the approach to them by the exponents of the Communist regime whose frequently vulgarizing opinions deeply and adversely afflicted the artist’s life and work. Filla faced various forms of persecution, in spite of which he managed to keep the post of professor at the Academy of Fine Arts in Prague for the rest of his life. The book has been published on the ocassion of the opening of a new permanent exhibition mounted in the Emil Filla Commemoration Hall at the Peruc chateau where the artist had spent his summers and that had played an important role in his late-life activities.
Keywords: Filla, Emil -- 1882-1953; Sammlung; Rezeption; Malerei; Kunst; Zeichnung; China; Filla, Emil / https://id.oclc.org/worldcat/entity/E39PBJj4tdTRyVCCbjJwm43G73; Painters; Art / Chinese influences; Art, Chinese / Private collections; Czech Republic / https://id.oclc.org/worldcat/entity/E39QbtfRpXBb3PtYpdKGBBHGQY; Criticism, interpretation, etc; Catalogs